Kinetics changes in total cholesterol predict HBeAg seroconversion in chronic hepatitis B patients treated with pegylated interferon‐alfa. Issue 4 (6th January 2023) - Cao, Xiongyue; Hu, Qiankun; Xu, Wei; Li, Qiang; Zhang, Jiming; Chen, Liang; Huang, Yuxian; Qi, Xun
Abstract: There is no satisfactory standard for predicting HBeAg seroconversion during Pegylated interferon alpha (PegIFNα) treatment. Studies have shown that IFNα therapy in chronic hepatitis C patients could alter serum lipid profiles. However, there have been no studies on lipid changes that predict the outcome of PegIFNα monotherapy in treated‐naive chronic hepatitis B (CHB) patients. This retrospective study included 130 treated‐naive HBeAg‐positive CHB patients receiving PegIFNα monotherapy. The relationship between serum lipid changes and HBeAg seroconversion was analysed. The TC‐ALT‐HBsAg‐HBeAg‐Genotype‐Age (CASEGA) model was established to predict HBeAg seroconversion after PegIFN‐α monotherapy. Among 130 patients, 33 achieved HBeAg seroconversion (SR) and 97 did not achieve HBeAg seroconversion (NR). The decrease in serum total cholesterol (TC) in the NR group was significantly higher than in the SR group at Week 24 (−9.59% vs. −0.31%, p < 0.001). Multivariate logistic regression analysis showed that the change in TC at Week 24 (odds ratio = 1.065, p = 0.009) was an independent predictor of HBeAg seroconversion. The area under the receiver operating characteristic curve for the CASEGA model was 0.883. The model score at the maximum Youden index was 90, and the specificity, sensitivity, positive predictive value and negative predictive value were 0.727, 0.794, 0.546 and 0.895, respectively. The HBeAg seroconversion rate at Week 72 in patients with scores >90 was significantly higher than that in patients with scores <90 (54.55% vs. 10.47%, p < 0.001). This study indicated that the change in the TC level at 24 weeks in CHB patients treated with PegIFNα was associated with HBeAg seroconversion. The CASEGA prediction model based on the TC change rate of 24 weeks has good predictive efficiency for HBeAg seroconversion.